PKM – Workshop Peningkatan Kapasitas dan Pemahaman Kemampuan Penelitian Tindakan Kelas bagi Guru Sekolah di Kabupaten Lebak - Dentik Karyaningsih (Jurnal Dharmabakti Nagri, 2023)
The objective of this activity is to improve the understanding and abilities of teachers in conducting classroom action research as a means to enhance the quality of education in schools. The workshop was conducted over two days and involved 30 participants from various schools in Lebak Regency. The results of this activity show that the workshop successfully increased the participants' capacity and understanding of classroom action research. Through pre-test and post-test assessments, a significant improvement was observed in the participants' comprehension of the concepts and steps involved in conducting classroom action research. The workshop materials, presented by competent facilitators using interactive and participative methods, provided a positive learning experience for the participants. The participants expressed their appreciation for the workshop and felt more prepared and confident in implementing classroom action research in their respective schools. The workshop achieved its intended objectives and brought positive benefits to the participants in enhancing the quality of education in Lebak Regency. In conclusion, this workshop successfully enhanced the capacity and understanding of classroom action research skills for school teachers in Lebak Regency. The workshop contributed positively to the development of education in the region and is expected to serve as a foundation for similar activities in the future, continually improving the quality of education and teacher competencies in Lebak Regency.